2017
DOI: 10.1037/ebs0000089
|View full text |Cite
|
Sign up to set email alerts
|

Daily relationship quality in same-sex couples: Attachment and sacrifice motives.

Abstract: Previous researchers examining romantic couples' dynamics have highlighted important behaviors, such as sacrifice motives, that can enhance or detract from relationship quality. It is equally as important to understand what individual characteristics contribute to these relationship behaviors. We examined how daily sacrifice motives (i.e., approach and avoidance) and attachment insecurity (i.e., anxiety and avoidance) interact to predict relationship quality in a sample of 81 same-sex couples (58 ϭ female, 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(80 reference statements)
0
12
0
2
Order By: Relevance
“…Relationship functioning was assessed using an abbreviated version of the Perceived Relationship Quality Component (PRQC) scale (Fletcher et al, 2000 ), a measure that has been used in studies of heterosexual couples (Muusses et al, 2015 ; Silva et al, 2017 ) as well as SMM couples (Cooper et al, 2017 ; Godfrey et al, 2021 ). The survey included four of the six PRCQ domains.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship functioning was assessed using an abbreviated version of the Perceived Relationship Quality Component (PRQC) scale (Fletcher et al, 2000 ), a measure that has been used in studies of heterosexual couples (Muusses et al, 2015 ; Silva et al, 2017 ) as well as SMM couples (Cooper et al, 2017 ; Godfrey et al, 2021 ). The survey included four of the six PRCQ domains.…”
Section: Methodsmentioning
confidence: 99%
“…Yet research within a GAR approach allows us to examine relationship dynamics in multiple contexts, comparing couples with two men or two women and testing whether his and hers marriages might extend to these contexts. These studies show that there are gender differences when comparing relationships between two men and two women in the determinants of relationship quality (Cooper et al, ; Pollitt, Robinson, & Umberson, ). For example, Pollitt et al (), in their study of midlife couples, found that greater gender conformity is associated with more shared power and with greater marital quality in same‐sex men couples and different‐sex couples, but not in same‐sex women couples.…”
Section: Applying a Gar Framework In Research On Aging Romantic Relatmentioning
confidence: 99%
“…In one of the first such studies, Wills, Weiss, and Patterson (1974) examined the association between partner behaviours over a 2-week period and global assessments of marital satisfaction (Laurenceau & Bolger, 2005). Diary studies have since been used to assess a variety of questions about intimate relationships, including how relationship satisfaction, intimacy, and functioning are influenced by factors such as attachment styles (Campbell, Simpson, Boldry, & Kashy, 2005;Cooper, Totenhagen, Curran, Randall, & Smith, 2017;Overall & Sibley, 2008), evaluation of and regard for one's partner (Kanat-Maymon, Argaman, & Roth, 2017;LeBel & Campbell, 2012), selfesteem (DeHart, Tennen, Armeli, Todd, & Affleck, 2008), negative interactions within the relationship (Li & Fung, 2013), time devoted to the relationship and to work (Repetti, 1989;Unger, Niessen, Sonnentag, Neff, 2014), and physical intimacy (Debrot, Schoebi, Perrez, & Horn, 2013).…”
Section: Processes Underlying Impaired Relationship Functioning In Social Anxietymentioning
confidence: 99%